Иранская мифологема царской власти и пектораль из Толстой Могилы - Полидович, Ю.Б. (Археологія і давня історія України, 2020)
Статья посвящена анализу изображений на золотой пекторали из кургана середины IV в. до н. э.
Толстая Могила. На основании изучения структуры пекторали, всех ее составляющих частей и на
сопоставлении изобразительных мотивов с иранской мифологией, предлагается новый вариант
интерпретации общего содержания изображений пекторали. The article is devoted to the analysis of images on
a gold pectoral from the Tovsta Mogyla of the middle
of the 4th century BC. The product has a well-thoughtout
structure (fig. 1). The main friezes are the internal
and external ones. The central axis on which the
most important scenes are located is highlighted. The
arrangement of the scenes inside the friezes is subject
to pendulum symmetry (fig. 2). The main theme of the
external frieze is the death. The central scene embodies
the triumph of death, but with each next scene it
recedes, and in scenes with a hare and grasshoppers
one can watch the transition of the theme to its opposite.
The main theme of the internal frieze is life.
The development of life is shown through the growth
of cubs from the moment of birth to the beginning of
adult life. Figures of birds on the frieze edges indicate
a change in theme. The story of man, which also has
its development, is interwoven into the internal frieze.
Its beginning is in the central scene where two men
create the clothes from sheep’s clothing. Such clothes
in Iranian mythology symbolized the royal khwarrah.
It can be assumed that the central characters are the
gods who create the royal khwarrah and the happy fate
of the future ruler. Such gods could be the Iranian Verethragna
and Mithra, corresponding to the Scythian
«Ares» and Oitosyros. In the three scenes of the upper
frieze the myth about royal power is enclosed. Its main
motives are following: predetermining the birth of the
king and his happy fate, birth, raising by shepherds,
being at the headquarters of the ruler after reaching
adulthood and gaining royal power. The appearance of
this mythology in the Iranian environment is probably
associated with the accession of Cyrus the Great and
the Achaemenid dynasty. In the Scythian environment
it was called upon to legitimize the power of the rulerowner
of the pectoral. Apparently the myth was a reference
to the legendary times of Kolaxais, the ancestor
of the Paralates, Scythian warriors and kings. In such
a situation the pectoral was conceived as one of the visible
incarnations of the royal family khwarrah, telling
by means of iconography about its origin. Стаття присвячена аналізу зображень на золотій
пекторалі з кургану Товста Могила середини IV ст. до
н. е.